Bot bannyāi kō̜n thēt lǣ panyuk samnūan nyuksamai - Sō̜nsai Bunpasœ̄t (Palindā kānphim, 2020)
Traditional of Lao sermonise Traditional Lao sermons, primarily focused on traditional medicine and healing in Theravāda Buddhist contexts
Keywords: Buddhist sermons; Health; Buddhist medicine